Falling Rain, Reigning Power in Reptilian Affairs: The Balancing of Religion and the Environment - Vargas-O’Bryan, Ivette (Religions of South Asia, 2013)
Animals such as the snake (in a herpetological reptilian sense and in its naga variety including the dragon) are prominent subjects in the Buddhist tradition. Snakes are not just partners to humans, or supports or hangings on temples, but are also central figures positioned to convey power struggles within and without the Buddhist tradition. As a Tibetan doctor makes sure he feeds the naga in the little house he built for it behind the hospital or the annual rituals on naga days indicate, there is recognition throughout South Asian Buddhism that nagas are not something to be ignored, but must be reckoned with, respected and incorporated into people's lives. Being possessed or inhabited by a klu (serpent) in the Tibetan medical texts or in a street in Dharamsala, India, indicates the real potential for lack of control and a loss of balance of power. Historically, Tibetan rituals to the klus were used to maintain political prominence, like the rituals rulers would conduct in ancient India and China to maintain the rains for their crops, often linked with ethical conduct, thus, fertile lands maintain a fertile rulership. Snakes in Buddhism command respect and serve as reminders of the ephemeral nature of existence. In juxtaposing ritual alongside narrative, medical and visual texts in the Buddhist traditions of India, Tibet and Nepal, this article will discuss how the presence of snakes have often been indicative of struggles to gain (or regain) prominence against other native traditions, to recover a cultural identity and to protect or create personal wealth, health or knowledge.